Interaction between physiological and subjective states predicts the effect of a judging panel on the postures of cellists in performance - Endo, Satoshi; Juhlberg, Kristina; Bradbury, Adrian; Wing, Alan M. (Frontiers in Psychology, 2014)
This study investigated the effect of a panel of judges on the movements and postures of cellists in performance. 24 expert cellists played a short piece of music, to a metronome beat, in the presence and absence of the panel. Kinematic analyses showed that in the presence of the panel the temporal execution of left arm shifting movements became less variable and closer to the metronome beat. In contrast, the panel's presence had no reliable effect on their spatial accuracy. A detailed postural analysis indicated that left elbow angle during execution of a given high note was correlated with level of heart rate, though the nature of this correlation was systematically affected by the relevant participant's subjective state: if anxious, a higher heart rate correlated with a more flexed elbow, if not anxious then with a more extended elbow. Our results suggest a change in physiological state alone does not reliably predict a change in behaviour in performing cellists, which instead depends on the interaction between physiological state and subjective experience of anxiety. This highlights a need to distinguish performance anxiety from physiological arousal, to which end we advocate currency for the specific term performance arousal to describe heightened physiological activity in a performer.